EXAMINING THE IMPACT OF PROJECT-BASED LEARNING ON STUDENT ENGAGEMENT AND CRITICAL THINKING SKILLS IN HIGH SCHOOL SCIENCE EDUCATION - Reyaz Ahmad Bhat (CV. Radja Publika, 2022)
Abstract This research paper investigates the effects of project-based learning (PBL) on student engagement and critical thinking skills in high school science education. The study explores how PBL, as an instructional approach, influences students' level of involvement and their ability to think critically within the context of science education. Through a mixed-methods research design, this paper provides valuable insights into the potential benefits of PBL in fostering meaningful learning experiences for high school science students.